Beginner's guide to animation - Murphy, Mary (New York : Watson-Guptill Publications, 2008)
An illustrated guide to creating low-budget two-dimensional stop-motion films, how to set up an animation station and make models, and how to film and edit.
About this book --Sec. 1 Setting Up --Sec. 2 Get Creative --Free Stuff --Resources --Glossary --Index --Credits.
Includes index.
"Everything you need to know to get started"--Cover.
Keywords: Animated films; Animation (Cinematography); Sculpture -- Technique